Applicability of M-Learning for basic Arabic language among students during distance learning - Yahaya, Mohd Firdaus; Ab. Halim, Zulazhan; Sahrir, Muhammad Sabri; Abdul Hamid, Mohd Fauzi; Mat Saad, Khoirun Nisak (Human Resource Management Academic Research Society, HRMARS, 2021)
One of the emerging strategies in education is the usage of mobile devices (PdP). Following this line of thought, Arabic courses make a point of emphasising the use of m-learning in PdP at the fundamental level. Due to the Covid-19 epidemic, this study was done to investigate – at the most basic level – the applicability of Arabic m-learning among students on distance learning. The research involved 147 individuals who were enrolled in basic Arabic language classes. The students were satisfied with the application of mTasheel in the PdP process, according to the findings. The studies also revealed that Google platforms like Docs, Slides, and Sites were among the best and most dependable applications to utilise during PdP sessions during distance learning especially during the Covid-19 pandemic